Transformation of Teosinte (Zea mays ssp. parviglumis) via Biolistic Bombardment of Seedling-Derived Callus Tissues - Zobrist, Jacob D.; Martin-Ortigosa, Susana; Lee, Keunsub; Azanu, Mercy K.; Ji, Q; Wang, Kan (Frontiers in Plant Science, 2021)
Modern maize exhibits a significantly different phenotype than its wild progenitor teosinte despite many genetic similarities. Of the many subspecies of Zea mays identified as teosinte, Zea mays ssp. parviglumis is the most closely related to domesticated maize. Understanding teosinte genes and their regulations can provide great insights into the maize domestication process and facilitate breeding for future crop improvement. However, a protocol of genetic transformation, which is essential for gene functional analyses, is not available in teosinte. In this study, we report the establishment of a robust callus induction and regeneration protocol using whorl segments of seedlings germinated from mature seeds of Zea parviglumis. We also report, for the first time, the production of fertile, transgenic teosinte plants using the particle bombardment. Using herbicide resistance genes such as mutant acetolactate synthase (Als) or bialaphos resistance (bar) as selectable markers, we achieved an average transformation frequency of 4.17% (percentage of independent transgenic events in total bombarded explants that produced callus). Expression of visual marker genes of red fluorescent protein tdTomato and β-glucuronidase (gus) could be detected in bombarded callus culture and in T1 and T2 progeny plants. The protocol established in this work provides a major enabling technology for research towards the understanding of this important plant in crop domestication.